Gene expression pattern of microbes associated with large cyanobacterial colonies for a whole year in Lake Taihu. (1st September 2022) - Shi, Limei; Cai, Yuanfeng; Gao, Shengling; Zhang, Min; Chen, Feizhou; Shi, Xiaoli; Yu, Yang; Lu, Yaping; Wu, Qinglong L.
Abstract: Large cyanobacterial colonies, which are unique niches for heterotrophic bacteria, are vital for blooming in eutrophic waters. However, the seasonal dynamics of molecular insights into microbes in these colonies remain unclear. Here, the community composition and metabolism pattern of microbes inhabiting large cyanobacterial colonies (> 120 µm, collected from Lake Taihu in China) were investigated monthly. The community structure of total microbes was mostly influenced by chlorophyll a (Chl a ), total phosphorus (TP) concentration, dissolved oxygen, and temperature, whereas the colony-associated bacteria (excluding Cyanobacteria) were mostly influenced by total organic carbon, NO3 −, and PO4 3− concentrations, indicating different response patterns of Cyanobacteria and the associated bacteria to water nutrient conditions. Metatranscriptomic data suggested that similar to that of Cyanobacteria, the gene expression patterns of the most active bacteria, such as Proteobacteria and Bacteroidetes, were not strictly dependent on season but separated by Chl a concentrations. Samples in July and September (high-bloom period) and February and March (non-bloom period) formed two distinct clusters, whereas those of other months (low-bloom period) clustered together. The accumulation of transcripts for pathways, such as phycobilisome from Cyanobacteria and bacterial chemotaxis and flagellum, phosphate metabolism, and sulfur oxidation from Proteobacteria, was enriched in high- and low-bloom periods than in non-bloom period. Network analyses revealed that Cyanobacteria and Proteobacteria exhibited coordinated transcriptional patterns in almost all divided modules. Modules had Cyanobacteria-dominated hub gene were positively correlated with temperature, Chl a, total dissolved phosphorus, and NH4 + and NO2 − concentrations, whereas modules had Proteobacteria-dominated hub gene were positively correlated with TP and PO4 3− . These results indicated labor division might exist in the colonies. This study provided metabolic insights into microbes in large cyanobacterial colonies and would support the understanding and management of the year-round cyanobacterial blooms. Graphical abstract: Image, graphical abstract